The analysis of economic transformation of a chosen post-socialist country (the case of Russia) - Molotkova, Daria; Šíma, Ondřej; Jankulár, Pavel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2026)
The bachelor's thesis focuses on the extent to which Russia’s dependence on oil and gas shaped its economic transformation after the collapse of the Soviet Union. The thesis aims to state whether resource dependence primarily served as a catalyst for accelerated stabilization and growth or as a structural constraint that obstructed diversification, productivity gains, and long-term resilience. The theoretical part of this work is dedicated to the definition and explanation of the leading theory of economic development and natural resources dependency in Russia over the period from 1991 to 2021. The empirical part consists of an analysis of oil and gas export and government revenue percentages, production levels, real and non-resource growth in GDP, and investment rates to support the chosen theories.
Vedoucí práce: Ondřej Šíma
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses